PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DI KEPENGHULUAN BANGKO PUSAKA KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Arisandi, Ridho; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Community participation of development is the participation of community in the development process both in the planning stage of development through musrenbangkep, the stage of development implementation, evaluate the development and in enjoying the results of development. Community participation in development planning through development planning discussion (musrenbang) is still minimal and passive, due to lack of community understanding of development planning, low education level, and lack of socialization from the government then excludes the community in development planning deliberations. Participation is used as Theory Concept. The researcher uses Soetomo Theory. This research aimed to know how the community participation of physical development in Kepenghuluan Bangko Jaya Bangko Pusako Subdistrict Rokan Hilir Regency. This research used Qualitative Method with descriptive study of data. Data was collecting by interviewed the key informant as information resource, observation, and documentation. The result showed that the community participation of physical development is still minimal and passive, that means there are still many people who are not involved in every stage of development that will be implemented and still submit all decisions to other parties. In this case the researcher suggested that the community should participate actively in every stages of development and the government should also seek more and active participation from community, so that the idea comes more from the community and it can be used as consideration and evaluation for the next year. Keywords: Participation, Community, Development.